Immune-checkpoint inhibitor resistance in patients with cancer - Luis Cabezón-Gutiérrez; Sara Custodio-Cabello; Magda Palka-Kotlowska; Beatriz Chacón-Ovejero; Vilma Pacheco-Barcia (Exploration of Immunology)
The introduction of immune checkpoint inhibitors (ICIs) has transformed the landscape of oncology, offering significant improvements in patient survival and achieving remarkable long-term outcomes. Despite these advances, the therapeutic benefits of ICIs are not universal, and existing biomarkers often fall short in accurately predicting patient responses. A comprehensive understanding of the mechanisms underlying resistance to ICIs is essential for the development of strategies to mitigate these challenges and enhance therapeutic efficacy. This review provides a detailed exploration of the resistance mechanisms associated with ICIs, focusing on the role of the tumor microenvironment and intrinsic tumor cell alterations in mediating both primary and secondary resistance. Furthermore, it evaluates emerging strategies to overcome resistance, including combination therapies and innovative therapeutic approaches. By dissecting the molecular and immunological pathways implicated in ICI resistance, this review aims to highlight novel predictive and prognostic biomarkers and outline optimized therapeutic strategies to maximize the clinical impact of ICIs in cancer management.